Rationale for enzymatic cavitation treatment of sewage sludge - Valentina A. Domracheva; Daria V. Vasilkovskaya (Водное хозяйство России: проблемы, технологии, управление)
At the present stage of development of society, protecting surface and underground water bodies from wastewater pollution is an important task. The main direction is the creation of effective technologies for the collection and purification of domestic, industrial and mixed wastewater, allowing the use of the sludge formed during treatment, depending on its composition and method of processing. Improving the quality of sewage sludge depends on the choice of method for its stabilization.